Feminism reimagined. Recoded. - Alkali, Muhammad; Talif, Rosli (Universiti Putra Malaysia Press, 2014)
The paper explored how in feminism, the sexes will co-exist to determine mutuality in the over-heated sexual polity. Series of sexual rift between the sexes have been the attention of extensive debate; and the debate still rages on as to whether taking series of the imagined aspects of feminism would still widely be viewed as working outside, or in this instance against feminism. With the emergence of recoded feminism (Nego-feminism), there is a significant shift from other previously coded feminisms because there are observable defective dichotomies. Based on the findings, therefore, the authors recommend that in sanitising the sexist world, it is important for both sexes to bury their egos and simply, in a round table discussion, negotiate their mutual existence. The authors synthesised that as an answer to all sexual challenges, if concerted efforts are not made by feminists, critics, and teachers of literature towards Nego-feminism, the world may continue to be beclouded by visions of disharmony between the sexes.